PELATIHAN LONCAT NAIK TURUN TRIBUN DAN PELATIHAN LONCAT NAIK TURUN BANGKU MENINGKATKAN DAYA LEDAK OTOT TUNGKAI PADA PESERTA EKSTRA KURIKULER BOLA VOLI PUTRA SMA NEGERI 1 TEGALLALANG - Budi Sudarsana, I Putu Agus; Pangkahila, J. Alex; Satriyasa, Bagus Komang; Weta, Wayan; Sandi, I Nengah; Ayu Dewi, Ni Nyoman (Sport and Fitness Journal; Volume 7, No.1, Januari 2019, 2019)
ABSTRACT This study was conducted to determine the increase in limb muscle explosive power. The training was conducted with 5 reps of 3 sets over six weeks in the field of Tegallalang 1 Public High School starting at 17.00 WITA until completion. In this study using 2 groups, namely the 1st group given jump training up and down the stands, the 2nd group was given jump training up and down the bench. The sample for each group is 8 people who have met the requirements of the male volleyball extra-curricular participants of Tegallalang 1 Public High School. Data from leg muscle explosive results obtained from 3 jumps taken before and after training. The results obtained before and after the Group-1 training were 57.5 cm to 70.875 cm and Group-2 were 57.375 cm to 65.75 cm. Hypothesis testing uses an independent t-test at a significance limit of 0.05 (p <0.05). Based on the differences in the results of the intergroup test analysis using independent t-test obtained group-1 and group-2 for p = 0.935 which showed no significant difference before being given treatment with a p value greater than 0.05. Whereas after treatment the group-1 and group-2 were obtained at p = 0.007 which showed a significant difference between groups 1 and 2 groups with a p value smaller than 0.05. It can be concluded that jumping up and down the stands is more effective than jump training up and down the bench in increasing the explosive power of the leg muscles. For this reason, it is expected that sports coaches to apply jumping up and down the stands as an alternative in increasing athletes' explosive power. Keywords: Training jumping up and down the stands, training jumping up and down the bench, explosive muscle power.